2005
DOI: 10.1095/biolreprod.104.031591
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for the Production of Transgenic Cloned Pigs: Electroporation-Mediated Gene Transfer to Non-Cultured Cells and Subsequent Selection with Puromycin1

Abstract: Puromycin N-acetyl transferase gene (pac), of which the gene product catalyzes antibiotic puromycin (an effective inhibitor of protein synthesis), has been widely used as a dominant selection marker in embryonic stem (ES) cell-mediated transgenesis. The present study is the first to report on the usefulness of puromycin for production of enhanced green fluorescent protein (EGFP) transgenic piglets after somatic cell cloning and embryo transfer. Somatic cells isolated from porcine fetuses at 73 days of gestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 23 publications
3
38
0
Order By: Relevance
“…Transgenic pigs expressing fluorescent cell markers have been generated by many research groups [7,8,27,[65][66][67][68][69][70][71][72][73][74][75][76]. For example, Webster et al [72] produced transgenic pigs that simultaneously expressed red fluorescent protein from Discosoma (DsRed), enhanced GFP (EGFP) and enhanced blue fluorescent protein (EBFP).…”
Section: Development Of Transgenic Pigs With Reporter Genesmentioning
confidence: 99%
“…Transgenic pigs expressing fluorescent cell markers have been generated by many research groups [7,8,27,[65][66][67][68][69][70][71][72][73][74][75][76]. For example, Webster et al [72] produced transgenic pigs that simultaneously expressed red fluorescent protein from Discosoma (DsRed), enhanced GFP (EGFP) and enhanced blue fluorescent protein (EBFP).…”
Section: Development Of Transgenic Pigs With Reporter Genesmentioning
confidence: 99%
“…Permanent genetic modification of somatic donor cells for SCNT has been achieved by random genomic insertion of plasmid DNA (Hyun et al 2003;Kragh et al 2009;Kragh et al 2004;Watanabe et al 2005) or by genomic integration of transduced retroviral or lentiviral vectors Park et al 2001;Park et al 2002). In both non-viral and viral approaches inclusion of a drug resistance gene in the transgene-encoding vectors allows selection for cells containing the integrated vector.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that one explanation for the failure to detect an antibiotic-resistant gene after selection is the so called 'by-stander effect' [4,7]; that is, expression of an antibiotic resistance gene in some cells could confer antibiotic resistance to nearby cells either by direct contact between cells or by secretion of the gene product into the medium. However, Watanabe et al [6] have reported that puromycin can be used for selection of recombinant cells from non-cultured cells.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between the two groups' observations was the donor cells used; Betthauser et al [7] used crossbred (Yorkshire/Landrace/ Berkshire cross)-derived donor cells, whereas Watanabe et al [6] used Landrace-derived donor cells. We used adult earderived fibroblast cells from a gnotobiotic miniature pig and four commercial pigs, including three inbred (Duroc, Landrace and Berkshire) pigs and one crossbred pig (Duroc × Landrace × Berkshire).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation